Complexities of colour: Black women negotiating space and identity in Braamfontein through skin-tone registers - Msibi, Siyanda Samukelisiwe Lindelwa (My University, 2020)
This study focusses on the meanings of skin-complexion for a group of young black women living and working in the inner city of Braamfontein. It investigates the various ways in which they come to negotiate, shape and form their identities within multiple spaces in the city. The study attempts to explore the kinds of terminology used to describe different contexts in which space and identity are negotiated, such as, the term “woke” and “yellow-bone”; and furthermore, investigated the weight and depth that these words carry in the social normative setting of Braamfontein life for these young women. The study makes use of an intersectional lens to engage these narrated experiences; just to understand in what ways the various skin-complexions of a black woman, including the yellow-bone, play a role in the spaces they are able to access within the inner city. Being a black South African woman in the context of diversity tends to be challenging for some in different settings. Skin-complexion has always been used as a significant measure that identifies a woman’s, worth in beauty. However, with various intersections at play, especially 25 years post-apartheid, the skin-complexions that one would expect to see in common places may have a different place now in modern society. Six themes emerged from the results, that explore how young black women come to perceive and understand their black identity in relation to the complexion of their skin; 1) Family perceptions of skin-complexion, 2) Self-perceptions of complexion and identity-preservation , 3. The missing middle, 4) Transforming stereotypes among various complexions, 5) The role of intellect on perceived complexions, 6) Dating men space. . Each theme addresses and uncovers different domains, affecting identity formation, through skin tone registers; beginning with family, at the cornerstone of identity for most. Gradually moving into perceptions of skin and self as this often plays a role in the degree to which people view their ability to gain access into a desired space. The study uncovers themes relating to a sense of non-belonging and identifies the impacts of this on identity. Finally, it explores the manifestations of potential relationships with the opposite sex. It would appear that the complexion of a black women’s skin, regulates perceptions of self in relation to others and further dictates the thoughts and impressions she has of herself as a black woman in urban society. Identity formation is an integral part of this study. In other words, our identities are formed by our experiences in life, both positive and negative. Who you are, no matter your skin tone or shade of black, as a black woman, you are defined by what society deems acceptable or not; pretty or not pretty; better light skinned or dark skinned; and the unfair and inaccurate assumptions made about your intellectual abilities based on your blackness or lack thereof
This report is submitted in fulfilment of the requirements for the degree of Masters in Community Counselling by coursework and research report in the faculty of Humanities in the University of the Witwatersrand, 2020